Protective effect of newly synthesized indole imines against ethanol-induced gastric ulcer in rats. Issue 1 (1st January 2021) - Akhtar, Muhammad Shoaib; Malik, Abdul; Arshad, Haroon; Batool, Sara; Raza, Abdul Rauf; Tabassum, Tahira; Murtaza, Mian Anjum; Riaz, Muhammad; Noreen, Misbah; Rasool, Ghulam
Abstract: Peptic ulcer is a common disorder of the gastrointestinal system affecting people of all ages worldwide. Ethanol is one of the most common causative agents for peptic ulcer. The aim of this study was to evaluate the protective effect of two newly synthesized indole imines (389 and 393) against ethanol-induced gastric ulcer in rats. Animals were orally administered different treatments: group I–II (vehicle & ulcer controls, respectively); 0.5% aqueous CMC solution, group III (standard control; omeprazole; 20 mg/kg bw); groups IV–VI, test compound 389 (20, 40 and 60 mg/kg bw) and groups VII–IX, test compound 393 (20, 40 and 60 mg/kg bw). Various parameters including pH, gastric contents, ulcer index and percentage protection were determined and histopathological study of gastric mucosa was performed to evaluate the protective effect of the test compounds. Oral administration of the test compounds, i.e. 389 and 393 (20, 40 and 60 mg/kg bw), significantly ( p  < 0.05) reduced the ulcer index in a dose-dependant manner as compared to the ethanol-induced ulcer control group. The gastroprotective potential of the studied test compounds was supported by the histological examination of the gastric mucosa showing a decreased inflammatory response with less oedema and leucocyte infiltration. The study concluded that the synthesized test compounds possess antiulcerogenic potential possibly due to their anti-inflammatory effects.